ANALYSIS OF SUPPLY CHAIN AND VALUE ADDED IN COCONUT MILK AGROINDUSTRY IN FANINDO TRADITIONAL MARKET BATU AJI DISTRICT BATAM CITY - Abdurrasyid, Raihan; Endaryanto, Teguh; Suryani, Ani (Jurnal Agristan, 2025)
This study aims to analyze the supply chain, supply chain performance, and value-added of coconut in coconut milk agro-industry in Fanindo Traditional Market, Batu Aji District, Batam City. The method used was case study. Respondents in this study consisted of agro-industry owners, coconut suppliers, and coconut farmers. The analysis method used was descriptive qualitative to answer the first objective, supply chain performance analysis method with marketing margin, farmer's share, and marketing efficiency approaches, and value-added analysis method. The results of this study show that the coconut supply chain consists of two channels, namely farmers - suppliers - agro-industry - consumers and farmers - agro-industry - consumers. The performance of the supply chain has been said to be efficient because the value of farmer's share of both channels 40%, namely 50,43% and marketing efficiency between 0-33% (8,31% at the supplier level and 0,40% at the agro-industry level) which means it is also in the efficient category. The value added generated is positive at Rp1,800,68/coconut (35,85%) which means that coconut milk agro-industry in Fanindo Traditional Market, Batu Aji District, Batam City is feasible to develop.